2016
DOI: 10.1111/brv.12263
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Paradox of Invasions revisited: the potential role of inbreeding × environment interactions in invasion success

Abstract: Invasive species that successfully establish, persist, and expand within an area of introduction, in spite of demographic bottlenecks that reduce their genetic diversity, represent a paradox. Bottlenecks should inhibit population growth and invasive expansion, as a decrease in genetic diversity should result in inbreeding depression, increased fixation of deleterious mutations by genetic drift (drift load), and reduced evolutionary potential to respond to novel selection pressures. Here, we focus on the proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 121 publications
3
113
0
Order By: Relevance
“…Population bottlenecks associated with colonization may lead to reduced genetic diversity, potentially limiting the ability of newly founded populations to adapt and persist (Frankham & Ralls, ; Lee, ). This genetic paradox in invasive species (i.e., how bottlenecked populations can still become successful) has intrigued researchers, who continue to explore possible mechanisms underlining this mystery (Frankham, ; Schrieber & Lachmuth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Population bottlenecks associated with colonization may lead to reduced genetic diversity, potentially limiting the ability of newly founded populations to adapt and persist (Frankham & Ralls, ; Lee, ). This genetic paradox in invasive species (i.e., how bottlenecked populations can still become successful) has intrigued researchers, who continue to explore possible mechanisms underlining this mystery (Frankham, ; Schrieber & Lachmuth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Murren & Dudash ; Mullarkey, Byers & Anderson ; Szűcs et al . ; Schrieber & Lachmuth ). During initial colonization and subsequent range expansion at the leading edges (Slatkin & Excoffier ; Hufbauer et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that non-native populations are often characterized by reduced genetic diversity compared with native populations due to bottlenecks during introduction (Sakai et al 2001, Hirsch et al 2011). Despite this, rapid evolution of non-native species may occur even when experiencing bottleneck events (Dlugosch and Parker 2008; Schrieber and Lachmuth 2016; Zenni et al 2016a, b, this issue). Some studies, however, provide evidence that reduced genetic diversity is not always the rule for non-native populations, and that genetic diversity can be maintained by different mechanisms dependent on introduction history (multiple vs. single introductions), native range genetic structure and propagule pressure (Petit et al 2004; Prentis et al 2008; Le Roux et al 2011; Mandák et al 2013).…”
Section: Introductionmentioning
confidence: 99%